Electrophysiological characteristics of epicardial breakthrough during catheter ablation of perimitral atrial flutter - Chhay, Chheng; Hsu, Chu-Yu; Chang, Shih-Lin; Lin, Yenn-Jiang; Lo, Li-Wei; Hu, Yu-Feng; Chung, Fa-Po; Chang, Ting-Yung; Lin, Chin-Yu; Hung, Yuan; Liu, Chih-Min; Kuo, Ling; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Unsuccessful endocardial ablation for peri-mitral atrial flutter (AFL) could be attributed by the epicardial bridging. Objective: This study aimed to investigate the electrophysiological characteristics of epicardial breakthrough during catheter ablation of peri-mitral AFL. Methods: This retrospective study recruited 40 patients who received successful catheter ablation of peri-mitral AFL from January 2016 to June 2021. The patients were divided into two groups: group 1 (n=18) successful endocardial ablation, and group 2 (n=22) successful epicardial ablation following unsuccessful endocardial ablation owing to incomplete mitral block or unachievable termination AFL. The local electrogram (EGM) interval of coronary sinus (CS) duration peri-mitral AFL was measured before catheter ablation. Results: There was no significant difference in the baseline characteristics between two groups. In group 2, 60% of successful epicardial ablation was performed in intra-CS ablation and 40% in VOM ethanol infusion. Group 2 patients had a longer EGM interval of distal CS than that in group1 (CS1-2: 64.2±17.5 vs. 42.4± 0.09 ms, P=0.008, CS3-4: 57.13 ± 19.4 vs. 43.8 ± 7.5 ms; P=0.001). The conduction velocity at successful site was slower in group 2 compare to group 1 (0.18 ± 0.05 vs. 0.75± 0.19 m/s, P=0.040). In the multivariate analysis, distal EGM interval (CS1-2) was identified as independent predictor of the need of epicardial ablation with the optimal cut-off of 49 ms. Conclusions: Longer EGM interval in distal-CS during peri-mitral AFL was observed in peri-mitral AFL patients with epicardial breakthrough following endocardial-failed ablation, which may be associated the need of epicardial ablation.